Facile one-pot synthesis of aliphatic bridged diaryloxy compounds, cyclic and crown ethers under mild conditions - Sakate, Sachin; Kamble, Sumit; Chikate, Rajiv; Rode, Chandrashekhar (Supramolecular Chemistry, 2017)
We report here the facile, room temperature, catalyst free, one pot synthesis of aliphatic bridged diaryloxy compounds, cyclic and crown ethers. Anhydrous potassium carbonate (K2CO3) as a mild base along with dimethyl sulfoxide generates the phenoxide ion which facilitates the nucleophilic substitution of bromoalkanes to yield the corresponding crown ethers.

Selective N-acetylation with concurrent S-oxidation of o-amino thiol at ambient conditions over Ce doped ZnO composite nanocrystallites - Jagtap, Rohidas; Sakate, Sachin; Pardeshi, Satish (Molecular Catalysis, 2018)
The oxidative S-S coupling of thiol to disulfide is an imperative chemical transformation in the domain of biological processes and also finds numerous chemical applications. The CeO2 and ZnO are significant catalysts for oxidation of thiol to disulfide and N-acetylation of amines respectively. Dithiobis(phenylene)bis(benzyldeneimine) moiety containing N-acetyl and disulfide functional groups is a potential antimicrobial agent with Leishmanicidal and antihyperlipidemic activities. Herein, we report a synchronized catalytic application of Ce doped ZnO (Ce-ZnO) and CeO2-Ce-ZnO composites for selective synthesis of Dithiobis(phenylene)bis(benzyldeneimine) from o-amino thiol. The Ce-ZnO samples were synthesized by simple co precipitation method by calcination of hydroxide precursors at 400 degrees C to get 0-10% Ce-ZnO nanocrystallites. The formation of CeO2-Ce-ZnO composite material was observed beyond 1.5% Ce concentration. The synthesized materials were well characterized by IR, XRD, DRS spectroscopy and SEM-EDS analysis. The application of Ce doped ZnO as an efficient catalyst towards the selective N-acetylation and concurrent S-oxidation of o-amino thiol to afford Dithiobis(phenylene)bis(benzyldeneimine) at ambient temperature in acetonitrile was deliberated. Among all screened catalysts, the maximum selectivity was found for 7.5% Ce-ZnO as CeO2-Ce-ZnO composite catalyst. Lewis acidic property of catalyst supported probable mechanism for achieved dual transformations. Also, the 7.5% Ce-ZnO catalyst has demonstrated a versatile S-S coupling ability for variety of thiol substrates with excellent stability.

Pyridine immobilised on magnetic silica as an efficient solid base catalyst for Knoevenagel condensation of furfural with acetyl acetone - Tarade, Komal; Shinde, Suhas; Sakate, Sachin; Rode, Chandrashekhar (Catalysis Communications, 2019)
Novel heterogeneous pyridine immobilised magnetic silica (Fe3O4@SiO2-Py) was found to be an efficient, greener and heterogeneous solid base catalyst for the Knoevenagel condensation of furfural with acetylacetone under optimized reaction conditions. The Knoevenagel condensation product 3-(2-furylmethylene)-2,4-pentanedione (FMP), a jet fuel precursor, was produced in high yield of 85% with 94% conversion of furfural at 100 degrees C within a period of 4 h. Fe3O4@SiO2-Py catalyst showed excellent stability and recyclability without losing its initial activity.
Keywords: furfural; Jet fuel; Knoevenagel condensation; Silica immobilised pyridine; Solid base